MiR-99a-5p up-regulates LDLR and functionally enhances LDL-C uptake via suppressing PCSK9 expression in human hepatocytes - Chen, Xuemei; Liu, Ying; Zhou, Qiujing; Zhang, Chenxi; Wang, Wei; Xu, Menglong; Zhao, Yaqiang; Zhao, Wenfeng; Gu, Dian; Tan, Shuhua (Frontiers in Genetics, 2024)
BackgroundMicroRNAs (miRs/miRNAs) play pivotal roles in modulating cholesterol homeostasis. Proprotein convertase subtilisin/kexin type 9 (PCSK9) binds to low-density lipoprotein receptor (LDLR) at the surface of hepatocytes and accelerates its degradation in lysosomes, thereby impairing the clearance of circulating low-density lipoprotein cholesterol (LDL-C) from plasma. Thus, suppressing PCSK9 expression level has become an effective approach for treating hypercholesterolemia. Here, we sought to identify novel miRNAs that inhibit PCSK9 expression.MethodsBy in silico analyses, miR-99a-5p was predicted to bind to human PCSK9 mRNA. Following transfection of miR-99a-5p or anti-miR-99a-5p in human and mouse hepatocytes, qRT-PCR, Western blot, immunofluorescence, ELISA, flow cytometry, LDL-C uptake, and cellular cholesterol measurement were performed.ResultsmiR-99a-5p overexpression potently inhibited PCSK9 expression, thereby up-regulating LDLR, functionally enhancing LDL-C uptake and increasing intracellular cholesterol levels in human, but not in mouse, cells. Conversely, anti-miR-99a-5p upregulates PCSK9, leading to a reduction in LDLR, attenuation of LDL-C uptake, and a decrease in the intracellular cholesterol levels of human hepatocytes. Furthermore, miR-99a-5p was shown to bind to the predicted target site “UACGGGU” in the 3′-UTR of human PCSK9 mRNA via a luciferase reporter assay in combination with site-directed mutagenesis.ConclusionMiR-99a-5p potently downregulates the expression of PCSK9 by directly interacting with a target site in the human PCSK9 3′-UTR, thereby up-regulating LDLR and functionally enhancing LDL-C uptake in human hepatocytes. MiR-99a-5p could serve as an inhibitor of PCSK9 for treating hypercholesterolemia to inhibit atherosclerosis.